A New Cyproheptadine PVC Ion Selective Electrode and their Applications in Pharmaceutical Preparations and Human Fluids - Q. Ismaeel, Yusur; A. Al-Phalahy, Bashaer (Al-Nahrain Journal of Science, 2020)
A simple, sensitive and rapid method for the determination of Cyproheptadine in the pharmaceutical preparations and human fluids. The construction and electrochemical response characteristics of a poly vinyl chloride (PVC) membrane selective electrode for the determination of CPH are described. The proposed sensor was composed of cyproheptadine-Bromophenol blue as ion-exchanger and Di-butylphthalate (DBPH) (electrode A), Tris (2-ethylhexyl) phosphate (TEHP) (electrode B) and Ortho-nitrophenyloctylether (ONPOE) (electrode C) as plasticizers. The slopes were 53.10, 58.72 and57.44 mV/decade for electrode A, B and C. The linear ranges were 1×10-5 - 1×10-2, 5×10-5 -1×10-2 and 5×10-5 -1×10-2 M and the detection limits were 9×10-6,4.5×10-5 and 4×10-5 M for Electrode A,B and C respectively. The electrode B based on TEHP showed the best results. Electrodes were successfully applied to the determination of the cyproheptadine in tablets and human fluids by direct and standard addition potentiometry.